Copper and arsenic accumulation of Pityrogramma calomelanos, Nephrolepis biserrata, and Cynodon dactylon in Cu- and Au- mine tailings - Menzuela Hidalgo Ancheta; M O Quimado; C L Tiburan Jr; A Doronila; E S Fernando (Journal of Degraded and Mining Lands Management, 2020)
Metallophytes are group of plants that can thrive on metal-rich substrate. These plants have potential in various green technologies. However, it is a must to first identify plants that can absorb heavy metals and tolerate the high concentration in their tissues. This study assessed the ability of plants thriving in a Cu-Au mined areas to uptake copper (Cu), and arsenic (As). The Cu and As content of the dried leaves, root tissues and soils were quantified using Atomic Absorption Spectrophotometer (AAS), and their bioaccumulation coefficient (BAC) were computed. Three species, Pityrogramma calomelanos, Cynodon dactylon and Nephrolepis biserrata, showed metal accumulation in the plant tissues. The three species have accumulation of Cu in the root and the estimated bioconcentration factor (BCF) is more than 1.0 which indicates the ability of these species to tolerate for said the metal hence is a good candidate for phytostabilization of polluted soils. Noteworthy was the accumulation of As in the shoot of the three species despite of the low soil As (<0.01 µg/g). Nephrolepis biserrata had the highest arsenic bioaccumulation factor of 30.91 followed by Cynodon dactylon (11.01) then Pityrogramma calomelanos (8.78) which make them potential species for clean-up of As through phytoextraction. Moreover, this study added C. dactylon as tolerant of arsenic in mined-out area in the Philippines.